Wade Keyes (Editor), Code of Alabama 1876 882 (1877), ch. 3, § 4109 - (:unkn) unknown (General Publisher, 1876)
Prohibited the carrying of a Bowie knife, pistol, or air gun, or any other weapon of “like kind or description,” unless threatened with or having good cause to fear an attack or while traveling or setting out on a journey. Punishable by a fine of $50-300 and imprisonment or hard labor for no more than 6 months.
--
Keywords: CARRY